Review of wide band-gap technology: power device, gate driver, and converter design - Ravinchandra, Krishna; Freddy, Tan Kheng Suan; Lee, June Seok; Lee, Kyo Beum; Mantooth, Homer Alan; Thiruchelvam, Vinesh; Xian, Jerome Ignatius Yuen Yi (Journal of Power Electronics, 2022)
This paper reviewed the state-of-the-art wide band-gap (WBG) technology from material level to system level. The properties of semiconductor materials, i.e., silicon carbide and gallium nitride, were investigated. The electrical characteristics of commercial power devices, which include static and dynamic performances, were assessed, and compared. The design requirements of WBG gate drivers were then underpinned, and various gate driver topologies were reviewed. Finally, their implementation in power electronic converters and performances were evaluated.
Keywords: Cascode; Converter design; Device gate; Electrical characteristic; Gate drivers; Power devices; Property; State of the art; System levels; Wide-band-gap; Cascode; Gallium nitride; Silicon carbide; Wide bandgap